Network Etiquette dalam Dakwah Digital pada Video Dakwah Kontroversial Gus Miftah - Dewi Putri Agung Jaya; Khairullah Khairullah; Umi Rojiati (Yayasan Literasi Sains Indonesia, 2026)
This study examines how network etiquette, in this context, refers to public reactions in the YouTube comment section to videos deemed offensive. This study aims to analyze network etiquette in digital da'wah on the YouTube social media platform. It is hoped that this study will produce Network Etiquette as a reference for responding to controversial da'wah videos in digital da'wah. The method used in this study is content analysis using a descriptive qualitative approach. Data collection begins with formulating the research problem, selecting samples, defining analytical categories, coding data, analyzing data, and interpreting the results. The results show that many comments still violate the principles of network etiquette, particularly regarding polite language. This is in line with the network etiquette theory of Rahmawati et al. (2022), which emphasizes the importance of applying the THINK concept before commenting, so that communication is ethical in the digital space. Furthermore, contextual analysis shows that the anonymity of YouTube users, which allows them the freedom to express emotions without considering social impact, contributes to low compliance with network etiquette.